"You just need to learn": A qualitative study on the information needs of family caregivers of people with lung cancer. (February 2022) - Cochrane, Andreanne; Gallagher, Pamela; Dunne, Simon
Abstract: Purpose: Lung cancer caregivers often face considerable duties and responsibilities yet frequently feel unprepared for this role. The current study is the first to purposefully explore the information needs of family caregivers throughout the lung cancer trajectory. Methods: Semi structured interviews were conducted with nine lung cancer caregivers (7 female) including those bereaved within five years. Interviews were transcribed verbatim and analysed using thematic analysis. Results: Four main themes emerged: 1) "He knew that I'd ask questions, you see": Information-gathering during appointments; 2) "You can't really ask that with mum there": Discordant information needs between caregiver and the person with lung cancer; 3) "Trying to get the answers": Seeking information beyond the hospital; 4) "It took a while to kind of get into": Learning to adjust to changing roles and circumstances. Conclusions: Lung cancer caregivers need reliable information to feel competent in their new roles and responsibilities. In the current study, there were a number of areas in which information was lacking, including those related to treatment, side effects, care services and symptom management. The provision of appropriate and timely information to lung cancer caregivers can ensure they feel supported in their roles and responsibilities. This will in turn benefit lung cancer survivors by ensuring that they understand information in consultations with oncology nurses and other health professionals and receive appropriate support from their caregivers that enhances their quality of life along the cancer trajectory. Highlights: This study purposefully explored lung cancer caregivers' information needs. Lung cancer caregivers may have discordant information needs from survivors. These caregivers need information on treatment, side effects, services & symptoms. They need reliable information to feel competent in their roles & responsibilities. Satisfying these information needs will in turn benefit lung cancer survivors.